Should we Bring Peacekeepers before the ICC? - Case Study of Burundi Peacekeepers - Hárs, András (The ICC at 25: Lessons Learnt, 2025)
Burundi has been a consistent participant in United Nations peace operations since the resolution of its domestic crisis in the mid-2000s. However, the conduct of its forces in multinational peace operations has come under significant scrutiny in the last decade, with recurring incidents of severe crimes, such as sexual exploitation and abuse being reported. Since the rule of law norms are precarious, with judicial independence being virtually nonexistent, the question of whether peacekeepers from Burundi should be tried for international crimes before the International Criminal Court arises. This chapter examines the overall legal situation, specifically regarding any jurisdictional difficulties that might arise, and offers a reality check from the decision makers’ perspective on the level of states and international organisations to highlight the positive and negative ramifications of trying peacekeepers before an international criminal tribunal.Keywords: International Criminal Court, jurisdiction, Burundi, peace operations, peace v. justice